0758 Behavioral Determinants of PAP Use in Veterans with COMISA: Results of a Randomized Trial. (25th May 2022) - Barretto, Bronson; Martin, Jennifer; Fung, Constance; Dzierzewski, Joseph; Stepnowsky, Carl; Song, Yeonsu; Zeidler, Michelle; Kelly, Monica; Enamorado, Daniel; Schnurrenberger, Jody; Josephson, Karen; Mitchell, Michael; et al.
Abstract: Introduction: Nonadherence to positive airway pressure (PAP) therapy is common in comorbid insomnia and obstructive sleep apnea (COMISA). We previously reported a novel behavioral treatment for COMISA which improves both PAP adherence and sleep. Our current goal was to assess whether improvements in PAP self-efficacy, knowledge, and decisional balance (targets of treatment) are associated with improvements in PAP use and sleep quality. We also collected participants' perceptions of benefits and challenges of PAP during intervention. Methods: 125 veterans (96% men, 39% non-Hispanic white, 24% Black, 17% Hispanic/Latino) with COMISA were randomized to a 5-week intervention integrating behavioral insomnia therapy with a PAP adherence program versus general sleep education (control). Objective PAP use data and Pittsburgh Sleep Quality Index (PSQI) were collected over 6 months. Three behavior change subscales (PAP Self-Efficacy [PAP-SE], Decisional Balance Index [DBI], Knowledge [KNOW]) were administered at 6-months. Weekly self-report of participant-perceived benefits and challenges of PAP use were collected among intervention participants. Subscale scores, PAP use and PSQI were compared between intervention and control, and associations were tested. Change in mean number of benefits and challenges of PAP use were also tested (all analyses intent-to-treat). Results: At 6-months, compared to controls, intervention participants had higher scores on all three subscales: PAP-SE (4.1 intervention versus 3.5 control, respectively), DBI (8.3, 0.9) and KNOW (10.5, 9.6, all p<.05). Intervention participants had more PAP use and lower (better) PSQI scores at 6-months (all p<.05). In the total sample, PAP use and PSQI correlated with PAP-SE (r=.52 PAP use, r=-.27 PSQI, respectively), DBI (r=.49, -.35) and KNOW (r=.43, -.21; all p<.05). Among intervention participants, perceived benefits of PAP increased over time (4.3 at week 2, 5.8 at week 4, respectively), and challenges decreased (3.7, 2.3; all p<.05). Conclusion: Behavioral treatment for COMISA improves behavioral determinants of PAP use, which is associated with improvements in PAP use and sleep quality. In addition, with treatment, perceived benefits of PAP increase and challenges decrease. These findings suggest improvements in self-efficacy, knowledge and perceived benefits of PAP are important mechanisms through which behavioral interventions improve PAP use in older adults with COMISA. Support (If Any): VAHSRD (IIR12–353-Alessi, RCSA20-191-Martin) and NIH (NHLBI K24HL143055-Martin, NIA K23AG049955-Dzierzewski)